2022
DOI: 10.1177/20503121221109911
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index in the first half of pregnancy and gestational diabetes: A systematic review

Abstract: Gestational diabetes mellitus is a more common complication in pregnancy and rising worldwide and screening for treating gestational diabetes mellitus is an opportunity for preventing its complications. Abnormal body mass index is the cause of many complications in pregnancy that is one of the major and modifiable risk factors in pregnancy too. This systematic review aimed to define the association between body mass index in the first half of pregnancy (before 20 weeks of gestation) and gestational diabetes me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…Lim et al [14] discovered that the TyG-BMI index outperformed TyG, TyG-WC, and TyG-WHtR in predicting IR. Recognizing that obesity, as de ned by BMI, is instrumental in IR progression [26] and implicated in GDM pathophysiology, higher maternal BMI emerges as a GDM risk factor [27,28]. Song et al [28] demonstrated that GDM likelihood escalates with each standard deviation increment in BMI (OR = 1.64, P = 5.05 × 10^-17).…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al [14] discovered that the TyG-BMI index outperformed TyG, TyG-WC, and TyG-WHtR in predicting IR. Recognizing that obesity, as de ned by BMI, is instrumental in IR progression [26] and implicated in GDM pathophysiology, higher maternal BMI emerges as a GDM risk factor [27,28]. Song et al [28] demonstrated that GDM likelihood escalates with each standard deviation increment in BMI (OR = 1.64, P = 5.05 × 10^-17).…”
Section: Discussionmentioning
confidence: 99%
“… 18 An elevated BMI carries an increased risk of GDM diagnosis. 19 In addition, multiparous females are more likely to develop GDM. 20 The median women in this study had a gravida/para designation of G3P2, signifying that most of the women in this study fall within the multiparous category and, therefore, are also at an elevated risk of developing GDM.…”
Section: Discussionmentioning
confidence: 99%
“…When reporting the article protocol, the PRISMA (preferential reporting items for systematic review and meta-analysis) guidelines were followed. (15,16) Also, according to PRISMA guidelines, the following steps were performed: systematic literature review, organizing documents to review, abstracting and evaluating the quality of each experimental study, combining data, and writing a report. (17)…”
Section: Methodsmentioning
confidence: 99%